(untitled) (Asian Journal of Social Science Studies, 2022)
The most convenient and efficient way to travel for the visually impaired is still with a guide dog. At present, my country’s legislation on the accessibility of guide dogs in public places is small in number, low in level, and unclear in legal responsibilities. There is still a gap between legislation and practice. In terms of safeguarding measures to enhance the accessibility of guide dogs to public places, we should first improve legislation, improve the qualification certification and marking system for guide dogs, and clarify the participants in disputes and their rights and obligations; second, we should strengthen judicial and supervision in the process of law enforcement, and promote the improvement of special procedures for the disabled and the community legal aid system. Once again, law enforcement should be improved, and cases should be handled flexibly; finally, the popularization of guide dogs should be strengthened for the society, and online information should be established online. Feedback platform to establish social service work points offline.